Shared and Distinct Phenotypes and Functions of Human CD161++ Vα7.2+ T Cell Subsets - Kurioka, Ayako; Jahun, Aminu S.; Hannaway, Rachel F.; Walker, Lucy J.; Fergusson, Joannah R.; Sverremark-Ekström, Eva; Corbett, Alexandra J.; Ussher, James E.; Willberg, Christian B.; Klenerman, Paul (Frontiers in Immunology, 2017)
Human Mucosal Associated Invariant T (MAIT) cells are an important T cell subset which are enriched in tissues and possess potent effector functions. Typically such cells are marked by their expression of Vα7.2-Jα33/Jα20/Jα12 T cell receptor (TCRs), and functionally they are major histocompatibility complex (MHC) class I-related protein 1 (MR1)-restricted, responding to bacterially-derived riboflavin synthesis intermediates. MAIT cells are contained within the CD161++Vα7.2+ T cell population, the majority of which express the CD8 receptor (CD8+), while a smaller fraction expresses neither CD8 or CD4 coreceptor (double negative; DN) and a further minority are CD4+. Whether these cells have distinct homing patterns, phenotype and functions has not been examined in detail. We used a combination of phenotypic staining and functional assays to address the similarities and differences between these CD161++Vα7.2+ T cell subsets. We find that most features are shared between CD8+ and DN CD161++Vα7.2+ T cells, with a small but detectable role evident for CD8 binding in tuning functional responsiveness. In contrast the CD4+CD161++Vα7.2+ T cell population, although showing MR1-dependent responsiveness to bacterial stimuli, display reduced T helper 1 (Th1) effector functions including cytolytic machinery, while retaining the capacity to secrete interleukin-4 (IL-4) and IL-13. This was consistent with underlying changes in transcription factor expression. Although we found that only a proportion of CD4+CD161++Vα7.2+ T cells stained for the MR1-tetramer, explaining some of the heterogeneity of CD4+CD161++Vα7.2+ T cells, these differences in transcription factor expression were shared with CD4+CD161++MR1-tetramer+ cells. These data reveal the functional diversity of human CD161++Vα7.2+ T cells and indicate potentially distinct roles for the different subsets in vivo.